2005
DOI: 10.1103/physrevb.72.214510
|View full text |Cite
|
Sign up to set email alerts
|

Evolution of superconductivity in electron-doped cuprates: Magneto-Raman spectroscopy

Abstract: The electron-doped cuprates Pr2−xCexCuO 4−δ (PCCO) and Nd2−xCexCuO 4−δ (NCCO) have been studied by electronic Raman spectroscopy across the entire region of the superconducting (SC) phase diagram. The SC pairing strength is found to be consistent with a weak-coupling regime except in the under-doped region where we observe an in-gap collective mode at 4.5kB Tc while the maximum amplitude of the SC gap is ≈ 8kBTc. In the normal state, doped carriers divide into coherent quasi-particles (QPs) and carriers that r… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

12
85
4

Year Published

2006
2006
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 64 publications
(101 citation statements)
references
References 68 publications
12
85
4
Order By: Relevance
“…Qazilbash et al 20 have shown from Raman spectroscopy measurements that superconductivity in the electron-doped is primarily due to pairing and condensation of hole-like carriers. It was also theoretically predicted that superconductivity will be favored by having hole states rather than electron ones at the Fermi energy 4 .…”
Section: Introductionmentioning
confidence: 99%
“…Qazilbash et al 20 have shown from Raman spectroscopy measurements that superconductivity in the electron-doped is primarily due to pairing and condensation of hole-like carriers. It was also theoretically predicted that superconductivity will be favored by having hole states rather than electron ones at the Fermi energy 4 .…”
Section: Introductionmentioning
confidence: 99%
“…Pairing symmetry of electron-doped high-T c cuprate superconductors such as Nd 2−x Ce x CuO 4 and Pr 2−x Ce x CuO 4 is a long standing problem [1,2,3,4,5,6,7,8,9,10,11,12,13,14,15,16,17]. Although no consensus has been reached yet, more and more recent experimental results have suggested that the order parameter of electron-doped cuprates is likely to have d x 2 −y 2 -wave pairing symmetry [1,2,3,5,9,10,14,16,17], in close resemblance to that of hole-doped materials.…”
Section: Introductionmentioning
confidence: 99%
“…Unfortunately, the superconducting gap of n-type cuprates is relatively small and determination of its exact value over a large doping range is an experimental challenge [12,13,14,15,16,17]. Previous estimates suggest that the superconducting pairing strength of the n-type cuprates is close to a weakcoupling regime in the optimally doped and overdoped region [18,19]. Furthermore, tunneling data suggest that …”
Section: Introductionmentioning
confidence: 99%